2016
DOI: 10.1123/ijspp.2015-0330
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Self-Reported Illness for Professional Team-Sport Athletes

Abstract: word count: 228Text-only word count: 3303 Number of tables: 2 Number of figures: 4 2 Abstract Purpose: The aim of this study was to identify contributing factors to the incidence of illness for professional team-sport athletes, utilizing training load (TL), self-reported illness and wellbeing data. Methods: Thirty-two professional rugby league players (26.0 ± 4.8 yr; 99.1 ± 9.6 kg; 1.84 ± 0.06 m) were recruited from the same club. Players participated in prescribed training and responded to a series of questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 23 publications
1
27
0
Order By: Relevance
“…Based on the results of the current study an increase of this amount in weekly or monthly TL would be accompanied by an increased illness risk of 50% and 54%, respectively. This is similar to studies in adult athletes which identified increased illness risk during times of increased weekly TL,26 28 29 31 and a recent systematic review which found a similar relationship in the majority of included studies of adult athletes 9. Our findings are also consistent with the only prior study of TL and illness in youth athletes of which we are aware found that increased training duration was associated with illness risk 24.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Based on the results of the current study an increase of this amount in weekly or monthly TL would be accompanied by an increased illness risk of 50% and 54%, respectively. This is similar to studies in adult athletes which identified increased illness risk during times of increased weekly TL,26 28 29 31 and a recent systematic review which found a similar relationship in the majority of included studies of adult athletes 9. Our findings are also consistent with the only prior study of TL and illness in youth athletes of which we are aware found that increased training duration was associated with illness risk 24.…”
Section: Discussionsupporting
confidence: 90%
“…In adult athletes, it has been suggested that higher volumes of exercise and impaired well-being may be associated with an increased susceptibility to viral infections 25–27. Illness in adult athletes from multiple sports has been associated with increased weekly TLs in some studies,26 28–30 but not others 31 32. However, there is a paucity of research in this area on youth athletes.…”
Section: Introductionmentioning
confidence: 99%
“…70 In elite crosscountry skiers, training monotony, reflecting little change in training load, was associated with a lower risk of illness, 3 but this was not confirmed in another 29-week prospective study in 32 rugby league players, where training monotony, together with overall increased internal load and load strain were all associated with an increased risk for self-reported illness. 79 In summary, there is some evidence that changes in external (increased volume and intensity of training) and internal training loads are associated with an increased risk of illness. However, given the current data it is not yet possible to quantify which amount of training load increase is related to increased risk of a specific illness, or in a specific sport.…”
Section: Evidence Relating Changes In Training Load and The Risk Of Imentioning
confidence: 99%
“…21,23,25 Further importance of ASRM and relationship with injury/illness has been observed in Rugby League, in this study fluctuations in ASRM between macrocycles were shown to provide useful insights into possible illness risk in players. 26 Further work is required to examine the relationships between ASRM and injury/illness risk in team-sport athletes.…”
Section: Athlete Self-report Measuresmentioning
confidence: 99%